An evaluation instrument and strategy implications of service attributes in LOHAS restaurants. Issue 1 (11th December 2018) - Cheng, Ching-Chan; Chang, Ya-Yuan; Tsai, Ming-Chun; Chen, Cheng-Ta; Tseng, Yu-Chun
Abstract : Purpose: This study aims to develop a comprehensive LOHAS (lifestyles of health and sustainability) restaurant service quality scale by using a rigorous qualitative and quantitative research process to effectively measure the service quality of LOHAS restaurants. Moreover, this study aims to further identify the Kano quality characteristics and strategic meanings of service attributes in LOHAS restaurants. Design/methodology/approach: This study designed the preliminary items of the service quality scale for LOHAS restaurants (LORSERV scale) based on relevant literatures and expert interview procedures. This study identified the goodness of fit of the questionnaire content, construct validity and validity of the LORSERV scale using exploratory factor analysis and confirmatory factor analysis. The moderated regression was conducted to identify the Kano quality characteristics and strategic meanings of each service attribute in LOHAS restaurants. Findings: The results indicated that the LORSERV scale included seven dimensions (internal sense of happiness, transitiveness, environment, healthy catering, service commitment, green practicability and thoughtfulness), for a total of 33 items. According to the results of the Kano model, the seven service attributes were categorized into the attractive quality. A total of 25 service attributes were categorized into the one-dimensional quality, and one service attribute was categorized into the must-be quality. Originality/value: The contribution of this study is that the scale could facilitate operators of LOHAS restaurants to effectively understand customer perceptions of service quality and serve as a reference to upgrade and improve service quality. The identification of Kano quality characteristics for each service attribute is conducive for LOHAS restaurants to understand the strategic meanings of each service attribute and can serve as a reference to make distinctive service strategies to reach sustainable operations.